The Late Antique Suburban Complex of Santa Giustina in Padua (North Italy): New Datings and New Interpretations of some Architectural Elements - Urbanová, Petra; Vedovetto, Paolo; Dilaria, Simone; Secco, Michele; Ricci, Giulia; Brogiolo, Gian Pietro (Hortus Artium Medievalium, 2022)
Abstract New research was recently conducted on the medieval remains of the religious complex of Santa Giustina in Padua (Italy) within the framework of the project ArchiDate. The latter, funded by the University of Padua, gathered scientists from the fields of art history, archaeology, material science and archaeometric dating of building materials. After several decades of debates, the chronological framework for two key ancient structures of the complex, San Prosdocimo’s chapel and the so-called ‘Opilio’s mausoleum’, was established thanks to the integration of mortar luminescence dating in the stratigraphical study of the architectural remains.